The effects of different pterygium morphology on anterior corneal curvature and predicting visual outcome - Mohd Radzi bin Hilmi (Kulliyyah of Allied Health Sciences, Intrnational Islamic University Malaysia, 2017)
This thesis aimed to investigate the effect of different pterygium morphology on anterior corneal curvature and predicting visual outcome after surgical intervention. A total of 93 primary pterygium participants were selected from patients who visited an ophthalmology clinic. This prospective cohort study involved pre and post-surgical assessment, with a total of 5 data collection sessions (Pre-surgical, 1, 3, 6, 12 months post-surgical. For pre-surgical, pterygium morphologies (redness, thickness, length, corneo-pterygium total area and dry weight were measured objectively. The association between pterygium morphologies (predictive factors) and predictive outcomes (SimK, CIM, SF, TKM, BCVA and CSF) were investigated. All participants underwent similar pterygium surgery procedures performed by a single surgeon. For all post-surgical assessment, identical measurements of topographic and clinical changes were made based on changes in its predictive outcomes. Comparisons in the magnitude changes between different types of pterygium were performed. Our result shows that fibro-connective components of pterygium were found able to provide the highest prediction with 27 – 55% of the predictive outcomes. With regards to types of pterygium, type III (fleshy) was found causing the biggest changes, followed by type II and I. Concisely, we found that single predictive factor is inadequate to either describe or predict changes on anterior corneal curvature and predicting visual outcome. We had demonstrated that utilizing pterygium morphologies, we were able to describe and predict changes in different types of pterygium better. We suggest that different types of pterygium would give rise to different magnitude changes on anterior corneal curvature and predicting visual outcome, thus we need to consider all pterygium morphologies in assessing pterygium.